Postoperative Upper Extremity Function in Implant and Autologous Breast Reconstruction - Alba, Brandon; Schultz, Benjamin; Qin, Lei Alexander; Cohen, Danielle; DelMauro, Matthew; Ahn, Soyouen; Kasabian, Armen K.; Perry, Adam D.; Tanna, Neil (Journal of Reconstructive Microsurgery, 2020)
Background After mastectomy and breast reconstruction, many patients experience upper extremity complications, such as pain, restriction in motion, and lymphedema. Despite an aesthetically satisfactory outcome, these occurrences can diminish a patient's postoperative quality of life. Several studies have investigated the causes and incidence of these complications. However, there is currently a paucity of data comparing postoperative upper extremity function according to reconstruction technique.Methods A review was performed of patients enrolled in a physical therapy (PT) program after mastectomy and immediate breast reconstruction. PT initial encounter evaluations were used to gather data on patients' postoperative upper extremity function. Hospital records were used to gather surgical and demographic data. For each patient, data were collected for each upper extremity that was ipsilateral to a reconstructed breast. Data were then compared between patients who underwent implant-based versus autologous deep inferior epigastric perforator flap reconstruction.Results A total of 72 patients were identified, including 39 autologous and 33 implant-based reconstruction cases. Proportions of patients who underwent sentinel lymph node biopsies and axillary lymph node dissections were similar between the two groups. The autologous-based reconstruction patients had significantly higher arm pain at rest (p = 0.004) and with activity (p = 0.031) compared with implant patients. Shoulder range of motion and manual muscle test results were similar between groups, with the exception of elbow flexion, which was weaker in implant patients (p = 0.030). Implant patients were also more likely to report “severe difficulty” or “inability” to perform activities of daily living (p = 0.022). Edema/swelling, axillary cording, and lymphedema girth measurements were similar between the two groups.Conclusion Different techniques of breast reconstruction can result in different postoperative upper extremity complications. These data show specific areas where postoperative care and PT can be customized according to reconstruction type. Investigation is currently underway to determine the effect of PT on upper extremity function in these patients.
Keywords: breast reconstruction; upper extremity; physical therapy